Mapping 18th and 19th Century Land Surveys - Boyko, Nicholas (Bulletin - Association of Canadian Map Libraries and Archives (ACMLA), 2026)
As Canada was settled by the British in the 18th and 19th centuries, a series of surveys were completed. These surveys divided the country into counties or divisions, and further into townships. As well, these surveys included information about the existing infrastructure and vegetation, giving a small picture of the land cover at the time. This last point is perhaps the most currently useful characteristic of the initial surveys; if mapped in GIS or by hand, the historic vegetation of the areas can be determined and compared to later 19th century surveys of the same format, as well as more modern 20th and 21st century data. This data flexibility can allow for much improved historic analysis. The following guide introduces the general data format and provides direction on the mapping of historic survey data.